2009
DOI: 10.1093/gerona/glp133
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Age-Related Metabolic Dysfunction in Mice With a Targeted Disruption of the C  Subunit of Protein Kinase A

Abstract: The cyclic adenosine monophosphate–dependent protein kinase A (PKA) pathway helps regulate both cell growth and division, and triglyceride storage and metabolism in response to nutrient status. Studies in yeast show that disruption of this pathway promotes longevity in a manner similar to caloric restriction. Because PKA is highly conserved, it can be studied in mammalian systems. This report describes the metabolic phenotype of mice lacking the PKA catalytic subunit Cβ. We confirmed that Cβ has high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 56 publications
1
35
0
Order By: Relevance
“…It is also reported that PPAR-␣-null mice show increased fatty acid accumulation and decreased cholesterol synthesis, glucose storage and gluconeogenesis in the liver with aging (36). In addition, with a diabetogenic diet, it is reported that plasma insulin level is increased with aging (37). Thus, it must be true that lipid metabolism is changed by aging.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that PPAR-␣-null mice show increased fatty acid accumulation and decreased cholesterol synthesis, glucose storage and gluconeogenesis in the liver with aging (36). In addition, with a diabetogenic diet, it is reported that plasma insulin level is increased with aging (37). Thus, it must be true that lipid metabolism is changed by aging.…”
Section: Discussionmentioning
confidence: 99%
“…RII thus represents a potential pharmacological target for the treatment of diet and age-induced obesity and fatty liver. Our studies have indicated that the C catalytic subunit of PKA also plays a role in maintaining a set point of adiposity (Enns et al, 2009b). Young C null mice appear overtly normal when maintained on a regular chow diet, but when challenged with a HF/HC diet, show resistance to the obesity and fatty liver disease suffered by their WT littermates.…”
Section: Pka and Obesity Resistancementioning
confidence: 70%
“…Plasma both total cholesterol as well as very low density and low density lipoproteins (VLDL and LDL) were significantly lower in RII null mice compared to WT (Schreyer, 2001). C null mutants, at least for males, when challenged with the HF/HC diet were resistant to the increases in LDL and VLDL and partially resistant to the increases in high density lipoprotein (HDL) observed in the serum of WT mice (Enns et al, 2009b). Because insulin inhibits the assembly and release of VLDLs from the liver (Koo & Montminy, 2006), it is possible that the reduced serum VLDL levels seen in both types of mutants is an indirect effect of their insulin sensitivity.…”
Section: Pka and Dyslipidemiamentioning
confidence: 95%
See 1 more Smart Citation
“…Transgenic mice that carry the middle T oncogene under the transcriptional control of the mouse mammary tumor virus promoter/ enhancer (MMTV-PyMT) develop widespread transformation of the mammary epithelium and the production of multi-focal mammary adenocarcinomas, with secondary metastasis to the lungs [7]. We developed a population of transgenic (MMTV-PyMT) 634Mul mice on a C57BL6/J background, a strain known to be obesity and diabetes sensitive when challenged with a high caloric diet [8]. Because we were interested in the role that obesity plays in tumor progression, rather than its contribution to increased cancer risk, we waited until tumors were palpable before switching mice to an HC diet.…”
Section: Introductionmentioning
confidence: 99%